RECONSTRUCTING CHILD CUSTODY POST-DIVORCE IN ISLAMIC FAMILY LAW: A BEST INTEREST OF THE CHILD-BASED APPROACH IN THE CONTEMPORARY ERA - Ushalli, Muhammad Uswah; Ushalli, Eskarni; Hayati, Naila; Ushalli, Lillahi (Ikatan Dosen Menulis, 2023)
The concept of child custody post-divorce has been a critical issue in Islamic family law, particularly in light of contemporary debates surrounding children’s rights and welfare. In recent decades, there has been a growing emphasis on the Best Interest of the Child (BIC) standard, which has shaped custody decisions in Western legal systems. This article explores the integration of the BIC principle within Islamic family law, specifically addressing how it can be reconstructed to align with modern child welfare needs. Through a comprehensive literature review, the paper examines Islamic legal sources, including the Qur’an, Hadith, and classical fiqh, to evaluate the traditional understanding of child custody in divorce cases. It further investigates the compatibility of Islamic principles with international human rights frameworks that advocate for the child's best interest. The article highlights the challenges and opportunities in adapting Islamic family law to contemporary child custody norms, considering cultural, legal, and societal factors. It also compares the Islamic approach with Western legal perspectives on child welfare, identifying areas for potential reform. The findings suggest that while Islamic law provides a strong foundation for protecting children's rights, it requires contextual adaptation to ensure the child’s best interests are consistently prioritized. This research calls for a balanced and progressive approach to reforming child custody practices within Islamic family law. Ultimately, it aims to contribute to a more child-centered framework in Islamic legal systems, offering insights for policymakers and legal practitioners.